Матеріали до «Словника фразеологічних синонімів Миколи Лукаша» - Цимбалюк-Скопненко, Т.; Скопненко, О. (Лексикографічний бюлетень, 2011)
This publication contains phraseological synonyms, taken from the translations of Mykola Lukash (registered аrticle безвихідь – бідувати). These registered articles have illustrative quotes from translated and original works of Mykola Lukash. Materials will be included in the future «Phraseological synonyms dictionary of Mykola Lukash».